2016
DOI: 10.1515/hmbci-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of FGF21 gene expression by metabolic factors and nutrients

Abstract: Fibroblast growth factor 21 (FGF21) gene expression is altered by a wide array of physiological, metabolic, and environmental factors. Among dietary factors, high dextrose, low protein, methionine restriction, short-chain fatty acids (butyric acid and lipoic acid), and all-trans-retinoic acid were repeatedly shown to induce FGF21 expression and circulating levels. These effects are usually more pronounced in liver or isolated hepatocytes than in adipose tissue or isolated fat cells. Although peroxisome prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 124 publications
(176 reference statements)
2
25
0
Order By: Relevance
“…Although a relationship between the expression of adipsin and FGF-21 has been reported [62], the regulatory factors at play still remain to be determined. FGF-21 is known to be regulated by a number of metabolic factors, nutrients, and oxidative stress [58,63,64], and involved in the regulation of glucose and lipid metabolism [65][66][67][68]. This could suggest that the lack of adipsin impacted these metabolic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although a relationship between the expression of adipsin and FGF-21 has been reported [62], the regulatory factors at play still remain to be determined. FGF-21 is known to be regulated by a number of metabolic factors, nutrients, and oxidative stress [58,63,64], and involved in the regulation of glucose and lipid metabolism [65][66][67][68]. This could suggest that the lack of adipsin impacted these metabolic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The chief player in this process is fibroblast growth factor 21 (FGF21). The studies on mice revealed that FGF21 is mainly produced in the liver and its expression is strongly upregulated by PPARα [44,45], but additional PPARα -independent transactivation mechanisms also exist, and involve retinoid orphan receptors (RORs) [46]. FGF21 activates hepatic lipolysis and ketogenesis in hepatocytes, and in various mammalian species is the chief endocrine factor driving metabolic reprogramming during torpor, which includes inhibition of cell growth in size and cell proliferation to preserve energy reserves [47].…”
Section: Nutrient-responsive Intracellular Signaling In the Regulamentioning
confidence: 99%
“…FGF21 has also been detected in human cerebrospinal fluid, indicating that circulating FGF21 may enter the brain to act on the central nervous system [19]. Recent reviews have summarized the production and secretion sites of FGF21 [20,21], the expression of its receptor components as well as FGF21 signaling pathway [22,23], and the metabolic [20,24] and pharmacological [25,26] effects FGF21 in mice and men. Thus, in this review we will focus on FGF21 levels in the blood of healthy, obese and metabolically unhealthy individuals to provide an overview on the concentration levels in human blood.…”
Section: Fgf21 Is a Hepatokinementioning
confidence: 99%